Spiritual Frameworks: Enhancing Student Discipline and Motivation through Islamic Organizational Culture - Ristianto, Fadjrie Mahardika; Tarifin, Ahmad; Nisa, Fakhrun; Syarifa, Ifta Nur; Muadibah, Ni’malul (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This study focuses on the influence of the integration of Islamic values in school organizational culture on student discipline and motivation in vocational schools. This study aims to explore how religious practices such as congregational prayers and morning prayers can shape students' character and improve the quality of their learning. The research method used is a qualitative approach with a case study design, which involves participatory observation, in-depth interviews, and documentation studies. The results of the study show that the Islamic values applied in this school play a significant role in increasing student discipline, responsibility, and motivation. These religious practices also create a conducive and harmonious learning environment, where students feel more focused and ready to learn. The implications of this study show that the integration of spiritual values in school culture can be an effective strategy in education management to improve academic achievement and shape the character of students with integrity